2011
DOI: 10.1002/srin.201100149
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Static Softening of Sintered MgO‐PSZ / TRIP‐matrix Composites with up to 10 vol.‐% ZrO2

Abstract: A metal matrix composite (MMC) consisting of AISI 304 austenitic stainless steel with up to 10 vol.‐% MgO‐PSZ was produced by a powder metallurgic process through sintering at 1300 °C and 1390 °C. The hot working of sintered samples was conducted between 900 °C and 1100 °C. The behaviour of softening kinetics was investigated using flow curve recording methods (dynamic softening) and the double‐hit method (static softening). The influence of the deformation parameters such as temperature, strain rate, inter‐pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Beside the infiltration of ceramic macrostructures by steel melts the powder metallurgy is another way of manufacturing these TRIP-matrix-composites in which all scopes of design are permitted. The authors had already published results for consolidation of these composites by means of conventional 2) and conductive sintering 3) as well as powder forging 4) and hot pressing.…”
Section: Introductionmentioning
confidence: 99%
“…Beside the infiltration of ceramic macrostructures by steel melts the powder metallurgy is another way of manufacturing these TRIP-matrix-composites in which all scopes of design are permitted. The authors had already published results for consolidation of these composites by means of conventional 2) and conductive sintering 3) as well as powder forging 4) and hot pressing.…”
Section: Introductionmentioning
confidence: 99%
“…The MgO‐PSZ shows a stress induced martensitic transformation from the tetragonal into the monocline phase which is accompanied by a volume increase leading to compressive stresses in the surrounding of the ZrO 2 ‐particles 11. The TRIP matrix composite material is produced both by two powder metallurgical (PM) routes (conventional sintering process 12, 13 and spark plasma sintering (SPS) process 14, 15) as well as by infiltration of ceramic preforms 16. So far, the steel matrix of the most PM variants is made of conventional metastable austenitic steel (AISI 304) in order to focus on the deformation and damage behaviour of the ZrO 2 ‐particles 12.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the area of cold forming, other effects such as the insufficient number of slip systems are predominant, which affects the general formability in a negative way. Prior tests with twin-roll-cast strips, however, have revealed that rolling with pass reductions of up to 20% at room temperature is possible [6]. Under these conditions no dynamic recrystallization can be expected.…”
Section: Texture Optimized Rollingmentioning
confidence: 99%